DEMAND FOR MONEY AND HAYEKIAN TRIANGLES - Potuzak, Pavel (REVISTA PROCESOS DE MERCADO, 2021)
Friedrich August von Hayek (1935) developed a specific business cycle theory in which interactions between the real and monetary sectors play a central role. In the first version of the theory, shocks to the money supply deflect market interest rate from the natural level and thus give false signals to entrepreneurs about relative demand between present goods and future goods. This idea was represented in a simple graphical tool, which was later called the Hayekian triangle. The structure of capital and the production process are depicted in a diagram that maps flows of resources from early stages of production to late stages, and finally to the hands of the consumer. On the basis of this theory, the prelimi- nary recommendation for the monetary authority was to freeze the money supply in order to prevent fluctuations in the structure of production (Hayek 1928).